Assistência à saúde mental no Programa Médico de Família de Niterói: uma cartografia - Carvalho, Kamilla de Andrade (2024)
This research had the challenge of investigating the production of mental health care in Primary Care in Niterói based on a Module of the Family Doctor Program, equipment that is configured as a device for decentralization and regionalization of the health system and is present in the most socially vulnerable areas of the municipality. To this end, we sought to identify the mental health care offers developed by a team from the Family Doctor Program, analyze how this care is produced and how the mental health matrix support process occurs. The cartography method made it possible to monitor and analyze, through participant observation and the construction of a field diary, the meetings and disagreements between health professionals and users. The research took place between December 2022 and March 2023, when it was possible to observe the daily life of the service, participate in home visits, mental health matrix meetings and a general meeting between specialized mental health care and Technical Managers in the region East-Oceanic. During the investigation, the topic of matrix support in mental health stood out and allowed us to identify that organizational problems such as lack of professionals, lack of time and work overload impact the participation of Primary Care professionals in matrix support. It was observed that there is a lack of greater understanding among Primary Care professionals and their managers regarding the purpose and responsibilities of matrix support. The matrix support meetings proved to be an important space for discussion, production and articulation of the network around mental health care.